Jaringan Marga sebagai Mesin Politik Pemenangan Bupati Terpilih Periode 2015-2020 - Haloho, Noprizal; ., Fitriyah; Marlina, Neni (Journal of Politic and Government Studies, 2017)
This research and analysis is for the sake of re-existence of the influence of equality relationship of marga / ethnicity in political system and its network as winner of Regent or commonly called with successful team 2015, and its power as political machine in Toba Samosir. The genus whose origin is the name of a person who is then named after the first name, is made so that they can understand each other from who can keep the marriage of a very clan descendant because it still has a blood relation. Then whether the political machine utilize relatives and similarities in the clan to campaign or realize the victory partner Ir. Darwin Siagian and Ir. Hulman Sitorus, MM.The research method using qualitative method. This study is a rare case elsewhere. Please note that any of these research procedures should produce descriptive data of speech and writing and the behavior of the observed. A qualitative approach is expected to produce in-depth descriptions of the words, writings, and / or observable behavior of a particular individual, group, society, or organization in a given context setting that is studied from a holistic, comprehensive, and holistic perspective. The informants were Team Success, Chairman of KPU, Regent / Vice Regent and Chairman of Adat.The research finds 3 important things that is, first how figure of candidate of Regent itself in public eye. The two ways of association of the clan network of candidate regents with political machine winning candidate pairs, and third is how the winning strategy is used. The conclusion of this research is the genus that has a real relationship with the political machine in Toba Samosir District.Keywords: Marga, Machine Politik , Regent